2020
DOI: 10.1002/adhm.202000353
|View full text |Cite|
|
Sign up to set email alerts
|

Modification of PLGA Scaffold by MSC‐Derived Extracellular Matrix Combats Macrophage Inflammation to Initiate Bone Regeneration via TGF‐β‐Induced Protein

Abstract: The immunologic response toward chronic inflammation or bone regeneration via the accumulation of M1 or M2 macrophages after injury could determine the fate of biomaterial. Human umbilical cord mesenchymal stem cells (hUCMSCs) have a pivotal immunomodulatory property on directing macrophage behaviors. Herein, for the first time, 3D‐printed poly(lactide‐co‐glycolide) (PLGA) scaffolds modified with hUCMSC‐derived extracellular matrix (PLGA‐ECM) are prepared by a facile tissue engineering technique with physical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 66 publications
0
57
0
Order By: Relevance
“…M1 macrophages can drive the inflammatory response, causing the scaffold to be wrapped in fibrous tissue, separating it from the surrounding tissue ( Fujihara et al, 2020 ). In contrast, M2 macrophages have anti-inflammatory properties and promote repair ( Ma et al, 2014 ; Hotchkiss et al, 2018 ; Deng et al, 2020 ).…”
Section: Immunological Characterization Of Biomaterialsmentioning
confidence: 99%
“…M1 macrophages can drive the inflammatory response, causing the scaffold to be wrapped in fibrous tissue, separating it from the surrounding tissue ( Fujihara et al, 2020 ). In contrast, M2 macrophages have anti-inflammatory properties and promote repair ( Ma et al, 2014 ; Hotchkiss et al, 2018 ; Deng et al, 2020 ).…”
Section: Immunological Characterization Of Biomaterialsmentioning
confidence: 99%
“…Promote lung cancer development Gazdic et al, 2017;Ren et al, 2019 (Continued) Frontiers in Cell and Developmental Biology | www.frontiersin.org Gong et al, 2016;Zhang et al, 2017;Deng et al, 2020; In vitro M2 macrophages, thereby forming a feedback pathway that enables MSC therapy improvement in hepatic injury (Bartosh et al, 2013;Lee et al, 2015;Reading et al, 2015;Luz-Crawford et al, 2016). Ko et al (2020) reported that macrophagederived amphiregulin is essential for MSC-mediated CD4+ T cell suppression and preserves epithelial stem cells to alleviate autoimmune uveoretinitis.…”
Section: Cutaneous Wound Healingmentioning
confidence: 99%
“…Gong et al (2016) also found that macrophage polarization plays an extremely important role in regulating MSC osteogenic differentiation to maintain bone homeostasis and bone regeneration. In addition, the MSCderived extracellular matrix alleviates macrophage inflammation to promote bone regeneration (Deng et al, 2020). Other studies have shown that for certain materials, the interaction between MSCs and macrophages includes the MSC-induced transformation macrophage phenotypes and macrophageinduced promotion of MSC differentiation; therefore, the physiological functions of MSCs and macrophages are regulated to improve osseointegration and promote bone repair (He et al, 2019;Mahon et al, 2020).…”
Section: Bone Tissue Repairmentioning
confidence: 99%
“…However, surface coating and plasma treatment can improve protein adsorption and enhance cell affinity [125]. Surface-modified bioprinted PLA and PLGA can provide a 3D cell culture environment for building various types of tissues [126][127][128].…”
Section: Polylactic Acid and Poly Lactic-co-glycolic Acidmentioning
confidence: 99%